2001
DOI: 10.1152/advances.2001.25.2.45
|View full text |Cite
|
Sign up to set email alerts
|

An Inquiry-Based Learning Model for an Exercise Physiology Laboratory Course

Abstract: We developed an inquiry-based learning model to better stimulate undergraduate students’ cognitive development of exercise physiology laboratory concepts. The course core is the two independent research projects that students, working in small groups, complete during the last 9 wk of the semester. Student groups develop their own research question and hypothesis, design the experiment, collect and analyze the data, and report their findings to the rest of the class using presentation software. To help with suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
31
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 1 publication
(1 reference statement)
9
31
0
2
Order By: Relevance
“…They are also consistent with the literature that has suggested that inquiry-based or constructivist methods promote learning in laboratory environments (Leonard, 1983;Crandall, 1997;Kolkhorst, 2001;Modell et al, 2000;Oliver-Hoyo, Allen, and Anderson, 2004;Travis and Lord, 2004), including one that focuses on the value of pre-laboratory discussions (Crandall, 1997). However, few of these have rigorous assessments.…”
Section: Discussion a Effectiveness Of Hplsupporting
confidence: 80%
“…They are also consistent with the literature that has suggested that inquiry-based or constructivist methods promote learning in laboratory environments (Leonard, 1983;Crandall, 1997;Kolkhorst, 2001;Modell et al, 2000;Oliver-Hoyo, Allen, and Anderson, 2004;Travis and Lord, 2004), including one that focuses on the value of pre-laboratory discussions (Crandall, 1997). However, few of these have rigorous assessments.…”
Section: Discussion a Effectiveness Of Hplsupporting
confidence: 80%
“…These judgements probably justify their opinion that the Basic Pharmacology practical activities should be considered in the course global qualifications to a larger extent. Similar findings have been observed in controlled studies of PBL-like activities in epidemiology (Dyke et al, 2001), pharmacology (Michel et al, 2002) and physiology (Kolkhorst et al, 2001), and could represent a typical side effect described for hybrid curriculum models (Steele et al, 2000;Kwan, 2002).…”
Section: Perception Of a Research Project-based Learning Activitysupporting
confidence: 84%
“…The carrying out of a research project as part of a problem-based learning programme has been successfully incorporated into the early phases of the biomedical curriculum in other institutions (Harrison, 1997;Østbye et al, 1998;Summers et al, 1998;Remes et al, 2000;Kolkhorst et al, 2001;Rangachari, 2002;Rivers, 2002;Smith, 2002). This activity seems to have a positive impact on students since they seem to be more motivated to pursue further scientific research and to develop an investigative approach to medical problems (Evered et al, 1987;Tollan & Magnus, 1993;Jacobs & Cross, 1995;Harrison, 1997;Summers et al, 1998;McManus et al, 1999;Remes et al, 2000) if compared with students who experience traditional lecture-based models of teaching (Kaufman & Mann, 1997).…”
Section: Perception Of a Research Project-based Learning Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Healey and Jenkins (2000), Healey (2005) and Justice, Rice, Roy, Hudspith, and Jenkins (2009) found that the inquiry-based approach increased student engagement in coursework. Kolkhorst, Mason, DiPasquale, Patterson, and Buono (2001) found that students enrolled in inquiry-based coursework were highly engaged and enthusiastic, and post-course journal entries, surveys, and interviews indicated that the students had a sense of empowerment and ownership in their work. Graduate assistants also reported a greater comprehension of the scientific process.…”
Section: Introductionmentioning
confidence: 99%